Noniterative Design of 2-Channel FIR Orthogonal Filters. (5th November 2006) - Jiménez Jiménez, M. Elena Domínguez M. Elena Domínguez
Abstract : This paper addresses the problem of obtaining an explicit expression of all real FIR paraunitary filters. In this work, we present a general parameterization of 2-channel FIR orthogonal filters. Unlike other approaches which make use of a lattice structure, we show that our technique designs any orthogonal filter directly, with no need of iteration procedures. Moreover, in order to design anL -tap 2-channel paraunitary filterbank, it suffices to chooseL / 2 independent parameters, and introduce them in a simple expression which provides the filter coefficients directly. Some examples illustrate how this new approach can be used for designing filters with certain desired properties. Further conditions can be eventually imposed on the parameters so as to design filters for specific applications.